Unusual Generation of Localized EPB in the Dawn Sector Triggered by a Moderate Geomagnetic Storm - Sripathi, S.; Abdu, M. A.; Patra, A. K.; Ghodpage, R. N. (My University, 2018)
An interesting piece of observation related to the equatorial plasma bubble (EPB) that is triggered by a geomagnetic storm at dawn sector on 4–5 February 2011 is presented. The storm activity was initiated at 17 UT when interplanetary magnetic field (IMF) Bz turned southward and the Dst index started decreasing (accompanied by AE intensifications) attaining its minimum at 70 nT. The IMF Bz presented large fluctuations marked by southward/northward transitions at slow and rapid rates and eventually returning to normal in the morning of 5 February. Observations from the very high frequency radar located at Gadanki, an off-equatorial station; an all-sky imager located at Kolhapur, a low-latitude station; and an ionosonde at Tirunelveli, an equatorial station, are analyzed to study the impact of this storm on the postmidnight to presunrise equatorial spread F. The results demonstrate that EPB irregularities can be generated by penetration electric field during what can be characterized as a moderate storm event. In contrast to prevailing belief, the present results show that EPB/equatorial spread F can be generated by undershielding electric field in the dawn sector, caused by an unusually delayed polarity reversal of the penetration electric field. The results further reveal oscillatory behavior in the height of F layer topside irregularities in association with IMF Bz oscillations. Observation of radar echoes from nighttime E layer irregularity structures and their Doppler velocities representing the penetration electric field polarity and intensity are also a notable finding of this paper.
Keywords: Geomagnetic storm; Equatorial Plasma bubble; EPBs